Hubungan tingkat stress dengan kejadian hipertensi - Sari, Maulida; Ahmady, Dedy; Roslaini, Roslaini; Wahyuni, Liza (Holistik Jurnal Kesehatan, 2025)
Background: One of the non-communicable diseases (NCDs) that is widely experienced by people in Indonesia is hypertension. Hypertension is one of the entry points or risk factors for diseases such as heart disease, kidney failure, diabetes mellitus, and stroke. One of the triggers for hypertension is the level of stress experienced by the community. Purpose: To determine the relationship between stress levels and the incidence of hypertension. Method: Analytical research design with a cross-sectional data collection approach. The population in this study were all patients who experienced hypertension in January - March 2024, in the Peusangan Health Center work area. The sampling technique used total sampling, namely 129 respondents. Data collection was carried out using a questionnaire and analyzed univariately and bivariately using the Pearson chi-square test. Results: Most were aged 60-74 years as many as 74 respondents (57.4%), were female as many as 93 respondents (72.1%), completed education up to high school / vocational school / MA as many as 78 respondents (60.5%), and worked as farmers as many as 51 respondents (39.5%). Most respondents did not have a family history of hypertension, namely 77 respondents (59.7%). However, most of them experienced hypertension, namely 69 respondents (53.5%) and experienced moderate stress, namely 100 respondents (77.5%). Based on the results of the chi square statistical test, a p value of 0.00 (<0.05) was obtained. Conclusion: There is a significant relationship between stress levels and the incidence of hypertension with a p value of 0.00 (<0.05). Suggestion: It is hoped that the community can reduce stress levels in their lives because it can trigger hypertension.   Keywords: Hypertension Incidence; Non-Communicable Diseases (NCDs); Stress.   Pendahuluan: Salah satu penyakit tidak menular (PTM) yang banyak dialami oleh masyarakat di Indonesia adalah hipertensi. Hipertensi merupakan salah satu pintu masuk atau faktor risiko penyakit seperti jantung, gagal ginjal, diabetes mellitus, dan strok. Faktor pemicu terjadinya hipertensi salah satunya akibat tingkat stress yang dialami oleh masyarakat. Tujuan: Untuk mengetahui hubungan tingkat stress dengan kejadian hipertensi. Metode: Desain penelitian analitik dengan pendekatan pengumpulan data cross sectional. Populasi dalam penelitian ini adalah seluruh pasien yang mengalami hipertensi pada bulan Januari – Maret 2024, di wilayah kerja Puskesmas Peusangan. Teknik pengambilan sampel menggunakan total sampling, yaitu sebanyak 129 responden. Pengumpulan data dilakukan dengan kuesioner dan dianalisis secara univariat dan bivariat menggunakan uji pearson chi square. Hasil: Sebagian besar berusia 60-74 tahun sebanyak 74 responden (57.4%), berjenis kelamin perempuan sebanyak 93 responden (72.1%), menamatkan pendidikan hingga SMA/SMK/MA sebanyak 78 responden (60.5%), dan bekerja sebagai petani sebanyak 51 responden (39.5%). Mayoritas responden tidak memiliki riwayat keluarga hipertensi berjumlah 77 responden (59.7%). Namun, sebagian besar mengalami hipertensi sebanyak 69 responden (53.5%)  dan mengalami stress sedang sebanyak 100 responden (77.5%). Berdasarkan hasil uji statistik chi square didapatkan p-value sebesar 0.00 (< 0.05). Simpulan: Ada hubungan yang signifikan antara tingkat stress dengan kejadian hipertensi dengan perolehan p-value sebesar 0.00 (< 0.05). Saran: Diharapkan masyarakat dapat mengurangi tingkat stress dalam berkehidupan karena dapat menjadi faktor pemicu terjadinya hipertensi.   Kata Kunci: Kejadian Hipertensi; Penyakit Tidak Menular (PTM); Stress.